Best practices in performing flow cytometry in a regulated environment: feedback from experience within the European Bioanalysis Forum. (August 2017) - der Strate, Barry van; Longdin, Robin; Geerlings, Marie; Bachmayer, Nora; Cavallin, Maria; Litwin, Virginia; Patel, Minesh; Passe-Coutrin, Wilfried; Schoelch, Corinna; Companjen, Arjen; Fjording, Marianne Scheel
Flow cytometry is a powerful tool that can be used for the support of (pre)clinical studies. Although various white papers are available that describe the set-up and validation of the instrumentation (the flow cytometer) and validation of flow cytometry methods, to date no guidelines exist that address the requirements for performing flow cytometry in a regulated environment. In this manuscript, the European Bioanalysis Forum presents additional practice guidance on the use of flow cytometry in the support of drug development programs and addresses areas that are not covered in the previous publications. The concepts presented here are based on the consensus of discussions in the European Bioanalysis Forum Topic Team 32, in meetings in Barcelona, Limelette and multiple telephone conferences.